2019
DOI: 10.1002/ijc.32108
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic PARP‐1 promotes pancreatic cancer tumorigenesis and resistance

Abstract: The poly(ADP‐ribose) polymerases (PARP) play important roles in repairing damaged DNA during intrinsic cell death. We recently linked PARP‐1 to death receptor (DR)‐activated extrinsic apoptosis, the present studies sought to elucidate the function of cytoplasmic PARP‐1 in pancreatic cancer tumorigenesis and therapy. Using human normal and pancreatic cancer tissues, we analyzed the prevalence of cytoplasmic PARP‐1 expression. In normal human pancreatic tissues, PARP‐1 expression was present in the nucleus; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Numerous human cancer cells, including pancreatic cancer cells, are resistant to TRAILinduced apoptosis and the molecular mechanisms underlying the resistance remain unclear, which makes it become a major huddle for the use of TRAIL-activating agents for cancer therapy despite its highly promising efficacy in targeting cancer cells. Our ongoing efforts in the search of strategies to sensitize TRAIL-induced apoptosis in resistant pancreatic cancer cells have uncovered that targeting the death inducing signaling complex (DISC) by either inducing expression of DR5 or converting survival signals to apoptotic singling is effective in promoting apoptosis of the TRAIL-resistant cancer cells 10,11,33,34 . The present studies offer novel molecular insights into sensitizing TRA-8-induced apoptosis of resistant pancreatic cancer cells at the essential initial step of the DISC formation, oligomerization of the death receptor, via inhibiting O-GlcNAcylation of DR5 ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous human cancer cells, including pancreatic cancer cells, are resistant to TRAILinduced apoptosis and the molecular mechanisms underlying the resistance remain unclear, which makes it become a major huddle for the use of TRAIL-activating agents for cancer therapy despite its highly promising efficacy in targeting cancer cells. Our ongoing efforts in the search of strategies to sensitize TRAIL-induced apoptosis in resistant pancreatic cancer cells have uncovered that targeting the death inducing signaling complex (DISC) by either inducing expression of DR5 or converting survival signals to apoptotic singling is effective in promoting apoptosis of the TRAIL-resistant cancer cells 10,11,33,34 . The present studies offer novel molecular insights into sensitizing TRA-8-induced apoptosis of resistant pancreatic cancer cells at the essential initial step of the DISC formation, oligomerization of the death receptor, via inhibiting O-GlcNAcylation of DR5 ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…The animal study protocol was approved by the Institutional Animal Care and Use Committee (IACUC) at the University of Alabama at Birmingham. Eight-week old male athymic mice (Jackson Laboratory) were used for tumor inoculation as we described 11,33,34 . Stable OGT knockdown (shOGT) or control cells (shScr) were inoculated subcutaneously into the flanks of mice (1.0 ×10 6 cells/site, 5 mice/each group).…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…PARP1 has also been shown to interact with mitofilin, a mitochondrial protein, and it localizes in mitochondria, where it plays a role in the maintenance of mitochondrial DNA integrity (21). Nuclear-cytoplasmic expression of PARP1 has also been shown to occur in breast cancer (33) and pancreatic cancer (34) in human patients. Additionally, PARP1 localization is cytoplasmic during HIV-1 Vpr expression in cells (35), which could indicate that proteins of other viruses also have the potential to change PARP1 localization.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed mechanistic insights revealed that cytoplasmic PARP-1 was recruited into the TRA-8-activated DISC and sustained Src-mediated pro-survival signals [11]. However, the knockdown of PARP-1 not only interfered with the activation of Src but also improved TRA-8-mediated apoptotic cell death in BxPc-3 and MiaPaCa-2 cells [11].…”
Section: Negative Regulators Of Trail-mediated Signalingmentioning
confidence: 99%